SMALL MULTIFIDUS MUSCLE SIZE PREDICTS FOOTBALL INJURIES. Issue 7 (11th March 2014) - Hides, J; Stanton, W; Smith, M; Mendis, D; Sexton, M
Abstract : Background: In Australian Football, hip, groin and thigh (HGT) muscle injuries have had the highest incidence and prevalence. A previous study showed that football players with relatively more severe pre-season 'HGT' injuries had a significantly smaller size of the multifidus muscle. Objective: This study was designed to examine the robustness of multifidus muscle measurements as a predictor of lower limb injuries incurred by Australian Football League players. Design: This was a prospective quasi-experimental research design. Muscle measurements were conducted at the start of the pre-season to predict pre-season injuries, and at the start of the playing season to predict injuries in the playing season. Setting: Players from 6 clubs of the Australian National football league were eligible for inclusion (n=275). Players were assessed on club premises. Participants: Assessments were conducted on 259 elite football players for the pre-season (94.2% of eligible players), and 261 players at the start the playing season (94.9%). Risk factor assessment: Morphology of the multifidus muscle was assessed using ultrasound imaging. Injury data were obtained from records collected by the AFL club staff during the pre-season and the playing season. Main outcome measurements: The dependent variable in the binomial logistic regression was occurrence of lower limb injuries in the pre-season and the playing season. Results: A lower limb injury was incurred by 38.2% of the players in the pre-season and 69.5% of the players in the playing season. A new model using cross-sectional area of the multifidus muscle reliably and consistently predicted lower limb injury in both the pre-season and playing season. In the season, 'kicking leg' was related to injury. Conclusions: The results of this study have established the predictive power of multifidus muscle size to predict injury in elite football players. These results provide a strong direction for clinicians who screen and treat athletes.